A methodology of informatics: the role of methodology in improvement of theory - Ona Voverienė (Knygotyra)
The article has a propounding character. Based on methodological literature, the essence of the concept "methodology" is revealed, explaining the role of scientific methods in knowledge and the role of methodology in improving theory and research work in some fields of knowledge. The results of the literature analysis are considered a starting point for investigating the methodology of informatics.